Infrared light elicits endothelium-dependent vasodilation in isolated occipital arteries of the rat via soluble guanylyl cyclase-dependent mechanisms - Lewis, Tristan H. J.; Zhuo, Junqi; McClellan, Jacob X.; Getsy, Paulina M.; Ryan, Rita M.; Jenkins, Michael. J.; Lewis, Stephen J. (Frontiers in Physiology, 2023)
The left and right occipital arteries provide blood supply to afferent cell bodies in the ipsilateral nodose and petrosal ganglia. This supply is free of an effective blood-ganglion barrier, so changes in occipital artery blood flow directly affect the access of circulating factors to the afferent cell bodies.The application of infrared (IR) light to modulate neural and other cell processes has yielded information about basic biological processes within tissues and is gaining traction as a potential therapy for a variety of disease processes. To address whether IR can directly modulate vascular function, we performed wire myography studies to determine the actions of IR on occipital arteries isolated from male Sprague-Dawley rats. Based on our previous research that functionally-important differences exist between occipital artery segments close to their origin at the external carotid artery (ECA) and those closer to the nodose ganglion, the occipital arteries were dissected into two segments, one closer to the ECA and the other closer to the nodose ganglion. Segments were constricted with 5-hydroxytryptamine to a level equal to 50% of the maximal response generated by the application of a high (80 mM) concentration of K + ions. The direct application of pulsed IR (1460 nm) for 5 seconds produced a rapid vasodilation in occipital arteries that was significantly more pronounced in segments closest to the ECA, although the ECA itself was minimally responsive. The vasodilation remained for a substantial time (at least 120 sec) after cessation of IR application. The vasodilation during and following cessation of the IR application was markedly diminished in occipital arteries denuded of the endothelium. In addition, the vasodilation elicited by IR in endothelium-intact occipital arteries was substantially reduced in the presence of a selective inhibitor of the nitric oxide-sensitive guanylate cyclase, 1H-[1,2,4]oxadiazolo [4,3-a]quinoxalin-1-one (ODQ).It appears that IR causes endothelium-dependent, nitric-oxide-mediated vasodilation in the occipital arteries of the rat. The ability of IR to generate rapid and sustained vasodilation may provide new therapeutic approaches for restoring or improving blood flow to targeted tissues.